2017
DOI: 10.1080/03043797.2017.1290585
|View full text |Cite
|
Sign up to set email alerts
|

The reflective diary as a method for the formative assessment of self-regulated learning

Abstract: Abstract. An increasingly desired outcome of engineering education is the ability to engage in selfregulated learning (SRL). One promising method for the formative assessment of SRL is the reflective diary. There is, however, a paucity of research on the use of reflective diaries in engineering education. To mitigate this gap, we report on a case study where reflective diaries were implemented in a master's course on tissue engineering. The objective of this paper is to explore the potential of reflective diar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 48 publications
1
66
0
2
Order By: Relevance
“…Current research reports the significance of writing reflective journals (Wallin & Adawi, 2017). However, Wallin and Adawi point out that, in higher education, most of reflective writing research comes from teacher education and nursing.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research reports the significance of writing reflective journals (Wallin & Adawi, 2017). However, Wallin and Adawi point out that, in higher education, most of reflective writing research comes from teacher education and nursing.…”
Section: Related Workmentioning
confidence: 99%
“…It also develops students' awareness of their own skills (Boud, Keogh, & Walker, 1998). Studies have shown that learning while reflecting on the metacognitive process is an important way of learning, however, it is not spontaneously learned and it must be taught (Wallin & Adawi, 2017). Giving learners the opportunities to reflect on their learning is a substantial way to focus learners and give them tools for improvement.…”
Section: Introductionmentioning
confidence: 99%
“…There are many types of research regarding reflective or learning journals such as science and technology (Çavuş, Özden, 2014;Cengiz, Karataş, 2014), mathematics (Hensberry, Jacobbe, 2012;Atasoy, Atasoy, 2006); teacher's practice (Alterman, 1965;Ekiz, 2006;Numrich, 1996;Gömleksiz, Sinan, Demir, 2010;Koç, Yıldız, 2012); teaching English as a foreign language (Barjesteh, Vaseghi, Gholami, 2011;Kır, 2012;Marefat, 2002); teaching Turkish to foreigners (Melanlıoğlu, Atalay, 2016); home studies (Güvenç, 2011); postgraduate (Tang, 2002); engineering (Wallin, Adawi, 2017); academic writing (Klimova, 2015). The use of the concepts of "reflective and learning logs" for a similar type of research in the literature can lead to a conceptual conflict.…”
Section: Introductionmentioning
confidence: 99%
“…It involves participants' describing over a period of time a recent experience and unpacking its salient aspects. This method has been used to study the experience of school-to-work transition in recent mechanical engineering graduates (Lutz & Paretti, 2019) and students' ability to engage in self-regulated learning (Wallin & Adawi, 2018). No speci c guidelines were given regarding the frequency and format of writing other than the general request that participants document their experiences and reactions during the rapid move of the university from face to face to online classes.…”
Section: Methodsmentioning
confidence: 99%